Christianity in Chinese Public Life: Religion, Society, and the Rule of Law - Carpenter, Joel A.; Dulk, Kevin R. den.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
This book analyzes the interaction of religion, society, and governance in China - suggesting it is much more subtle and complex than common convention suggests. The edited work addresses civic engagement, religion, Christianity, and the rule of law in contemporary Chinese society.
Keywords: Science; Science; Science, general